2007
DOI: 10.1186/ar2198
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated cellular senescence in degenerate intervertebral discs: a possible role in the pathogenesis of intervertebral disc degeneration

Abstract: Current evidence implicates intervertebral disc degeneration as a major cause of low back pain, although its pathogenesis is poorly understood. Numerous characteristic features of disc degeneration mimic those seen during ageing but appear to occur at an accelerated rate. We hypothesised that this is due to accelerated cellular senescence, which causes fundamental changes in the ability of disc cells to maintain the intervertebral disc (IVD) matrix, thus leading to IVD degeneration. Cells isolated from non-deg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
412
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 413 publications
(430 citation statements)
references
References 41 publications
16
412
1
1
Order By: Relevance
“…However, after proliferation disc cells may become senescent [6,12,18], a common finding in herniated discs [31]. Both Hsp27 and Hsp72 have been implicated in the regulation of cell proliferation, apoptosis and senescence [for reviews see 16 and 33].…”
Section: Discussionmentioning
confidence: 99%
“…However, after proliferation disc cells may become senescent [6,12,18], a common finding in herniated discs [31]. Both Hsp27 and Hsp72 have been implicated in the regulation of cell proliferation, apoptosis and senescence [for reviews see 16 and 33].…”
Section: Discussionmentioning
confidence: 99%
“…Degenerative changes triggered by such intrinsic or extrinsic factors creates a stressful microenvironment for the disc cells and possibly reprograms it to increase synthesis of inflammatory cytokines [6,55] and may even allow it to enter into stages such as senescence [56,57]. The presence of senescence in the human disc cells has been shown by culturing them with B-galactosidase, and a recent study has shown that mean telomere length of the disc cells decreases as cellular expression of P16INK4A increases [58]. These studies show that cell senescence plays a direct role in disc aging and degeneration.…”
Section: Changes In Disc Cells With Advancing Degenerationmentioning
confidence: 99%
“…These proteins aid in disc homoeostasis by blocking nerve ingrowth5 and disc calcification 6. Aberrant apoptosis within the nucleus pulposus is a key factor in the development of IDD and has been considered as a target for the treatment of disc degeneration 7, 8, 9…”
Section: Introductionmentioning
confidence: 99%